DEVELOPMENT OF SECURITY DETECTION USING A WIRELESS SENSOR NETWORKS (WSN) - MASROL, AMIRUL ALIF (2017)
Wireless Sensor Network (WSN) is one of the advance technologies which is deployed for various applications due to its low cost and remote monitoring ability. It is able to measure physical and environmental variables. This project designs a WSN for security detection in a small-scale area such as office room and laboratory to alert the user from intruders. The design of this project is based on multi-hop concept of WSN using ZigBee technology. Sensor nodes consist of microcontroller, ZigBee, motion sensor and power supply. A gateway node is connected to the computer to record gathered data variables which are the presence of human and sound produced by buzzer.